2003
DOI: 10.1007/s00261-002-0071-x
|View full text |Cite
|
Sign up to set email alerts
|

Management of branch duct-type intraductal papillary mucinous tumor of the pancreas based on magnetic resonance imaging

Abstract: MRI was useful to identify nonmalignant IPMTs of the branch duct type, and close follow-up observation with serial MRI examinations may be appropriate in the management of such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…MRCP is currently being investigated as the preferred imaging modality for diagnosis and follow-up of branch duct IPMNs of the pancreas [4,5]. CT remains the most commonly used imaging method, as well as the initial method of choice for evaluating patients with pancreatic disease.…”
mentioning
confidence: 99%
“…MRCP is currently being investigated as the preferred imaging modality for diagnosis and follow-up of branch duct IPMNs of the pancreas [4,5]. CT remains the most commonly used imaging method, as well as the initial method of choice for evaluating patients with pancreatic disease.…”
mentioning
confidence: 99%
“…Many reports have described the imaging fi ndings to determine the likelihood of malignancy, and one of the acceptable predictive signs for malignancy is the presence of mural nodules 3,9,11 (papillary projection with a diameter of ≥3 mm 6,10,12 or ≥5 mm 13 ) within the tumor. Other signs for malignancy are dilation of the main pancreatic duct (<5 mm, 9 ≥7 mm, 6 or 12 mm 12 ), entire lesion size ≥30 mm 6,11-13 , and so on.…”
Section: Discussionmentioning
confidence: 99%
“…However, malignant IPMT is often resectable and has a more favorable prognosis than IDAC. 6-10 Some investigators have reported that a good prognosis is limited until the lesions are noninvasive carcinoma 4,9,10,12,14,15 or invasive stage I IPMT. 16 Conlon reported that the 5-year survival rate of IPMT patients was 83%-100% for noninvasive carcinoma cases and 44%-65% for invasive car-A B D C Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, correct evaluation of IPMN is extremely important as a recent analysis has suggested that this entity is one of the few surgically curable pancreatic neoplasms [18] . Prior investigations showed MRI with MRCP was useful for assessment of IPMN as a noninvasive approach [23,35,36] . However, its spatial resolution is not as high as that of CT.…”
Section: Discussionmentioning
confidence: 99%